Periostin as a novel biomarker of cardiovascular disease: A systematic evidence landscape of preclinical and clinical studies. Issue 4 (25th November 2019) - Azharuddin, Md; Adil, Mohammad; Ghosh, Pinaki; Kapur, Prem; Sharma, Manju
Abstract: Background: Periostin is a matricellular protein, expressed in various normal adult and fetal tissues. Recently, elevated periostin levels have been reported in heart failure, coronary artery disease, and stroke. However, there is lack of clinical studies to clarify the prognostic significance of systemic periostin levels in cardiovascular diseases (CVDs). The aim of the study was to perform a systematic review of published evidence on periostin and CVDs, and to clarify the diagnostic and prognostic significance of systemic periostin levels in CVDs. Methods: A systematic search on PubMed was performed to identify relevant articles from inception to December 2018. The eligible studies evaluating the periostin expression and periostin levels in animal and human studies. Results: A total of 24 relevant studies, including both animal and human data, were included. Periostin is significantly observed in myocardium tissue of failing hearts compared with control, and is also expressed in atherosclerotic plaques. Systemic periostin levels were significantly correlated with cardiac function and severity of CVD in several studies. A clinical study also observed positive correlation between periostin and N‐terminal pro b‐type natriuretic peptide (NT‐proBNP), highly sensitive troponin (hsTnT), and ST2 cardiac biomarker. Studies reported limited adjustment for potential confounders. Conclusions: The evidence of current review support potential role of periostin in the pathophysiology of CVD. However, scarcity of data regarding the clinical use of periostin levels in the current management of CVDs further creates room for the future investigation. Therefore, further studies warrant to clarify its potential role, if any, as a novel cardiac biomarker.